Lifelong cumulative incidence of acquired aortic stenosis and its predictors in a large middle-aged men population followed up to 42 years. (25th November 2020) - Kontogeorgos, S.M; Thunstrom, E; Lappas, G; Rosengren, A; Fu, M
Abstract: Background: Acquired aortic stenosis (AS) is the most common valvular disorder that rises exponentially with age; it has high mortality after symptoms appear. Factors that predict the development of AS are still unknown. Some studies imply that the atherosclerotic factors are involved in the development of AS, but the findings have been heterogeneous. Purpose: To estimate lifelong cumulative incidence of AS and analyse its predictors. Methods: We included a random sample of men, born 1915–1925 in Gothenburg, Sweden, and examined them in 1970–1973 (participation rate 75%). They were between 47 and 55 years in the beginning and 57–65 years when the examination-period ended. Out of 7493 men 57 were excluded due to myocardial infarction prior to baseline; 7436 were thus followed from the inclusion date until a discharge diagnosis of AS or death, with a maximum follow up time of 42 years and mean follow-up time 26.8 years. Men with AS were identified from the Swedish National Patient Register and those who died from the Swedish Cause of Death Register. We used machine learning to identify the most important factors that predict AS. For these factors, we then estimated hazard ratios for the risk to acquire AS through Cox proportional hazards model. Results: The lifelong cumulative incidence to acquire AS was 2.66% (198 out of 7436 individuals). For men with measurements approximately at the quartiles of the pulse pressure distribution, more specifically 44, 52, 62 mm Hg, the estimated cumulative risk were 1.97%, 2.74% and 3.07% respectively. For the body mass index (BMI) we had accordingly for measurements around 23, 25 and 27 kg/m 2 estimated cumulative risk 2.52%, 2.80%, 2.79% respectively. For cholesterol values of 5, 6 and 7 mmol/l (approximately at quartile divisions) the estimated cumulative risk was 1.77%, 1.79% and 3.20% respectively. The estimated cumulative risks for the younger, with age around 47 and the older participants, with age around 55 were 1.76% and 2.68 respectively. Men with family history of infarction in a sibling had an estimated cumulative risk at 4.66% level whereas those with not at 2.51%. The factors that were significantly associated with the development of AS in the Cox proportional model are: cholesterol level (HR=1.24, CI 95% 1.11–1.39, p=0.0001), pulse pressure (HR=1.01, CI 95% 1.01–1.02, p=0.0037), BMI (HR=1.06, CI 95% 1.02–1.11, p=0.0089), age (HR=1.11, CI 95% 1.04–1.19, p=0.0010) and family history of myocardial infarction in a sibling (HR=2.38, CI 95% 1.50–3.79, p=0.0002). Conclusion: Lifelong cumulative incidence of acquired AS is approximately 2.7%. Multiple factors known also to be associated with arteriosclerosis were identified to increase the life-long risk of developing AS. Funding Acknowledgement: Type of funding source: None